2011
DOI: 10.1039/c1lc20067d
|View full text |Cite
|
Sign up to set email alerts
|

Single cell 3-D platform to study ligand mobility in cell–cell contact

Abstract: Lateral mobility and dimensionality have both been shown to influence cellular behavior, but have yet to be combined and applied in a single in vitro platform to address, e.g., cell adhesion in a setting mimicking the three-dimensional environment of neighboring cells in a reductionist way. To study the effect of the lateral mobility of cell adhesive ligands in three dimensions we present and characterize a platform, which enables patterning of single cells into microwells presenting a cell membrane mimetic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 50 publications
(56 reference statements)
2
58
0
Order By: Relevance
“…The all-or-nothing nature of junction formation combined with the observed sensitivity to supported membrane mobility and active cellular processes indicates an active nucleation step, which can be defeated if the supported membrane E-cadherin exhibits too much freedom of motion. Previous efforts to reconstitute cadherin in supported bilayers have used an Fc-conjugated extracellular domain of E-cadherin linked to the bilayer via either GPI or biotin−streptavidin interaction (24)(25)(26). As will be directly evidenced in the results presented here, these early efforts most likely did not achieve the nucleation threshold required to establish extended E-cadherin-mediated junctions.…”
Section: Significancementioning
confidence: 53%
“…The all-or-nothing nature of junction formation combined with the observed sensitivity to supported membrane mobility and active cellular processes indicates an active nucleation step, which can be defeated if the supported membrane E-cadherin exhibits too much freedom of motion. Previous efforts to reconstitute cadherin in supported bilayers have used an Fc-conjugated extracellular domain of E-cadherin linked to the bilayer via either GPI or biotin−streptavidin interaction (24)(25)(26). As will be directly evidenced in the results presented here, these early efforts most likely did not achieve the nucleation threshold required to establish extended E-cadherin-mediated junctions.…”
Section: Significancementioning
confidence: 53%
“…Prior reductionist assays have elucidated the role of cadherins in cell-cell junction dynamics using 2D substrates conjugated with purified N-cadherin or E-cadherin (17-21), 2D substrates copatterned with E-cadherin and extracellular matrix (ECM) (15,22), or 3D microwells containing single cells uniformly coated with a single protein type (23,24). However, none of these interfaces are designed to be homotypic to epithelial cells, because 2D copatterned surfaces lack the 3D geometry of a native junction and microwells coated with a single protein lack the bifunctionality of native junctions (basal ECM vs. lateral cadherin adhesions).…”
mentioning
confidence: 99%
“…Previous QCM-D analysis of gel-state SLBs in the presence of serum showed negligible protein fouling on such surfaces. [ 23 ] In addition, a cell adhesion study performed on polymerized zwitterionic SLBs consisting of Bis-SorbPC showed a high degree of cell repellence towards murine-derived macrophages despite the absence of lipid lateral mobility. [ 46 ] Clearly, signifi cant fouling was observed on gel-state SLBs and SAM PEG layers, whereas on the liquid-state SLB no fouling was observed in the case of nonspecifi c adhesion of ConA.…”
Section: Selection Of a Nonfouling Mv-functionalized Layermentioning
confidence: 99%